CONCEPTUALIZATION OF URBANIZATION STRUCTURE AND CLIMATE CHANGE IN LAGOS, NIGERIA - Adejobi Oladepo Samson; Olorunnimbe Rafiu O (Faculty of Geography, Universitas Gadjah Mada, 2011)
Urbanization is synonymous with environmental challenges. In developing countries, thechallenges have assumed higher dimensions proportionally due to multifarious issues of rapidchanges in the environment, due to development, through population growth andindustrialization, and accompanied by all kinds of pollution such as air pollution, wastedisposal, land use degradation, and vehicular pollution as the resultant effects of man’sinteraction with the environment. The main characteristic effect is the raised temperature of thecity centre (UHI) leading to excessive energy use for cooling and putting urban population atgreat morbidity and mortality risks. This paper literally explores the conceptual framework ofinteraction between urbanization structure and understanding social impacts of climate changeand variability for the evaluation of strategies in the urbanized environment that might serve asadaptive response to climate change. The urbanization structure that affects Lagos state isdiscussed in relation to the location of the city, the size, the population density, urbangeometry, thermal property, air pollution, land use pattern, wind speed and anthropogenicactivities. The study revealed that climate change is posing increasing challenges for citiesplacing greater stress and impacts on multiple social and biophysical systems, including urbaninfrastructure, water and energy demand simultaneously, followed by a strong global trendtowards urbanization of urban poverty. The study concluded that climate change has impactedgreatly on virtually all the socio-economic aspects of man.